Breakthrough in former socialistic economies : Case Wärtsilä Oyj - Hukkanen, Valtteri (My University, 2020)
The future market situations force companies to dynamically evolve and adapt strategies that will boost sales and provide value, without forgetting the customer focus. There is a need for multidivisional international companies to critically view and adapt their strategies so that they are easy to follow and provides the needed edge in the markets they operate in. This thesis investigated the market potential and a strategic guideline to be implemented into the sales for two countries located in Central Asia. The thesis was made for Wärtsilä Energy Business and particularly Wärtsilä Business Development and Sales East Europe as a case study. The case company needs to find new business areas to explore, as the countries in this thesis have a big potential to create new revenue streams. Wärtsilä Energy Business has a good foothold in countries with IPPs, however, it is important to find a strategy for breaking the markets in 0-IPP countries. The thesis consisted of scientific research about how and why to make a breakthrough sales strategy to increase the revenue flow taken in consideration the customers. This thesis also goes through the reasons why these two countries in Central Asia were chosen and how their energy sector looks like. The methodology used for this thesis was a case study where qualitative and quantitative research were concluded. In the quantitative research the thesis went through the target countries energy markets and the way they are possible heading. Energy market stochastic analysis was made with a simulation program called Plexos. The qualitative study was made with a benchmarking interview with other Finnish multidivisional company operating in these areas where the results of the interview was conducted to a PESTEL model. Other strategic tool to gather the key points and put them in a clear way for both countries was the use of business model canvas. The results of this thesis show that Wärtsilä should primary focus on engine sales and later integrate the renewable energy. The reason for this is that the markets are highly dependable of the gas price, which is steered by the government of the country. Plexos model gave us an understanding to find a balance between cost and C0₂ emissions. Also, a local presence or CRM should be established to fully understand the customer and have the ability to act proactively to a problem.
Keywords: Strategy, sales, customer, value, energy; fi=Tuotantotalous (tekniikka)|en=Industrial Management and Engineering|; Master's Programme in Industrial Systems Analytics